2010
DOI: 10.1158/1055-9965.epi-10-0287
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free Circulating DNA Is a Useful Biomarker to Distinguish Benign versus Malignant Prostate Disease

Abstract: Background: Free circulating DNA (fcDNA) has been shown to be elevated in serum of prostate cancer patients compared with benign controls. However, studies evaluating the role of fcDNA as a biomarker in a "representative" patient group who have undergone prostate cancer screening are lacking. Our study examined the use of serum fcDNA levels as a biomarker of prostate cancer in such a setting.Methods: The study included 252 men, with prostate-specific antigen (PSA) levels >4 ng/mL and/or abnormal digital rectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
(50 reference statements)
2
25
0
Order By: Relevance
“…On the other hand, during necrosis, apoptosis, autophagy and mitochondrial catastrophe, the tumour cells release DNA fragments of different sizes, which leads to raised levels of circulating cell-free DNA with longer fragments in serum or plasma 21. These studies have shown the existence of elevated levels of circulating cell-free DNA, probably released from cancer cells into the plasma or serum, which occurs in several types of cancer, such as lung,13 14 22 23 renal,9 prostate,28 29 breast,16 19 21 26 27 and CRC 15 18 20 25…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, during necrosis, apoptosis, autophagy and mitochondrial catastrophe, the tumour cells release DNA fragments of different sizes, which leads to raised levels of circulating cell-free DNA with longer fragments in serum or plasma 21. These studies have shown the existence of elevated levels of circulating cell-free DNA, probably released from cancer cells into the plasma or serum, which occurs in several types of cancer, such as lung,13 14 22 23 renal,9 prostate,28 29 breast,16 19 21 26 27 and CRC 15 18 20 25…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported, that patients with PSA of ≤10 ng/mL and cell-free DNA of > 180 ng/mL were at increased risk for prostate cancer compared with those with DNA of ≤180 ng/mL. Summing up, these findings show that cellfree DNA improved the specificity of prostate cancer screening and might, therefore, reduce the number of unnecessary prostate biopsies (Gordian et al, 2010). Ellinger et al designed a study to evaluate the apoptosis index which expresses the ratio of prostaglandin-endoperoxide synthase 2 (PTGS2) to Reprimo DNA fragments.…”
Section: Cell-free Genomic Dnamentioning
confidence: 63%
“…A recent nested case-control study, carried out in multiple populations, reported significantly high sPSA levels in patients with PCa as compared to healthy men (69). Further, the sPSA levels were also found to be highest in PCa than in healthy men (72) or BPH patients (176), irrespective of the racial diversity. The combined results of three separate recent Indian studies also show the sPSA levels to be highest in PCa, intermediate in BPH and lowest in healthy conditions (50,177,178).…”
Section: Utility Of Spsp94 In Association With Spsa For Differential mentioning
confidence: 94%